Corruption among Public Officials: What is the Oversight and View of Administrative Law? - Hamdun Hamdillah (LEGAL BRIEF, 2021)
The spread of corruption among political elites has actually become a planned habit, even now that corruption has begun to decentralize to regional and local level officials, acts of corruption actually occur with awareness, intention, and willingness to commit fraud. The role of administrative law in supervision in the field of public services, especially in the matter of public welfare services, basically functions as a supervisor in order to reduce the number of corrupt practices in Indonesia, especially in the scope of the bureaucracy and public government institutions. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that, bureaucratic reform which is illustrated through fair and equitable public services, is the beginning of awareness of public service mechanisms as well as a milestone in the government's awareness to organize its government system so that it runs smoothly. fair and wise, the spirit of reform that characterizes the utilization of the state apparatus is directed at realizing state administration that is able to support the smooth and integrated implementation of the duties and functions of administering government in a fair and wise manner, the legal aspects of state administration are part of the legal domain that directly influences efforts to realize reform public bureaucracy. This global change is based on universal value standards that can increase the government's participation in providing the best service for the wider community.